Impact of the COVID-19 pandemic on continuity of medical treatment for patients with chronic diseases in Japan: a retrospective cohort analysis - Tomoki Ishikawa; Akihito Kako; Jumpei Sato; Junko Hattori; Hiromasa Yoshimoto; Masaru Kitsuregawa; Kazuo Goda; Yoshimitsu Takahashi; Takeo Nakayama; Naohiro Mitsutake (BMC Health Services Research)
Abstract Background The COVID-19 pandemic has raised concerns about continuity of care for chronic diseases such as diabetes, hypertension, and dyslipidemia. Although studies have documented declines in healthcare utilization, few have assessed individual-level patterns of treatment interruption. Methods We conducted a retrospective cohort analysis using administrative claims data (2018–2021) from a Prefecture, Japan. Eligible patients were diagnosed with and prescribed medications for diabetes mellitus, hypertension, or dyslipidemia in January of 2019 or 2020 and followed until December of each year. The primary outcome was the time-to- interruption of physician visits, defined as a gap of at least 60 days between follow-up visits. We used Cox proportional hazards regression, adjusted for age, sex, comorbidities, and prior healthcare utilization, to compare the risk of treatment interruption in 2020 (COVID-19 group) vs. 2019 (pre-pandemic group). Sensitivity analyses were performed with thresholds of 30 and 90 days. Logistic regression examined whether pandemic-related interruptions were associated with the likelihood of returning to treatment within one year. Results A total of 410,911 patients met the inclusion criteria. Across all three chronic conditions, the hazard of interruption was significantly higher in 2020 than in 2019; adjusted HRs are 1.26 (95% CI = 1.17–1.36) for diabetes, 1.39 (95%CI = 1.31–1.47) for hypertension, and 1.24 (95%CI = 1.17–1.32) for dyslipidemia, respectively. No significant difference in resuming care was observed between the 2020 and 2019 interruptions (OR = 0.89; 95% CI = 0.81–1.09). Sensitivity analyses showed consistent findings, despite slight variations in hazard ratios for different gap thresholds. Conclusions The COVID-19 pandemic was associated with an increased risk of treatment interruption in patients with chronic diseases, underscoring the need for targeted strategies to maintain care continuity during public health emergencies. While older patients and those with multimorbidity showed earlier interruptions, the overall patterns persisted across disease groups, emphasizing the importance of preemptive measures and patient outreach to prevent delayed or forgone care.